The association between hope, marital status, depression and persistent pain in men and women following cardiac surgery - Ann Kristin Bjørnnes; Monica Parry; Irene Lie; Ragnhild Falk; Marit Leegaard; Tone Rustøen (BMC, 2018)
Abstract Background Cardiac surgery is a major life event, and outcomes after surgery are associated with men's and women's ability to self-manage and cope with their cardiac condition in everyday life. Hope is suggested to impact cardiac health by having a positive effect on how adults cope with and adapt to illness and recommended lifestyle changes. Methods We did a secondary analysis of 416 individuals (23% women) undergoing elective coronary artery bypass graft and/or valve surgery between March 2012 and September 2013 enrolled in randomized controlled trial. Hope was assessed using The Herth Hope Index (HHI) at three, six and 12 months following cardiac surgery. Linear mixed model analyses were performed to explore associations after cardiac surgery between hope, marital status, depression, persistent pain, and surgical procedure. Results For the total sample, no statistically significant difference between global hope scores from 3 to 12 months was observed (ranging from 38.3 ± 5.1 at 3 months to 38.7 ± 5.1 at 12 months), and no differences between men and women were observed at any time points. However, 3 out of 12 individual items on the HHI were associated with significantly lower scores in women: #1) I have a positive outlook toward life, #3) I feel all alone, and #6) I feel scared about my future. Over the study period, diminished hope was associated with older age, lower education, depression prior to surgery, and persistent pain at all measurement points. Isolated valve surgery was positively associated with hope. While neither sex nor marital status, as main effects, demonstrated significant associations with hope, women who were divorced/widowed/single were significantly more likely to have lower hope scores over the study period. Conclusion Addressing pain and depression, and promoting hope, particularly for women living alone may be important targets for interventions to improve outcomes following cardiac surgery. Trial registration Clinical Trials gov Identifier: NCT01976403 . Date of registration: November 28, 2011.